(untitled) (@limentech, Ciencia y Tecnología Alimentaria, 2023)
Volume 21, number 1 of 2023 of the @limentech Magazine is dedicated to the dissemination of knowledge in Food Science and Technology, presenting research by various authors. Topics such as the addition of ahuyama flour to improve vitamin A intake, the modeling of bacterial growth in coastal cheese, and the use of gellan in Lactobacillus delbrueckii are addressed. Methods of fruit preservation with edible coatings and the use of mango residues are also being explored. This research seeks to enrich the agri-food landscape and contribute to address food insecurity, in line with the objectives of FAO and WHO. The scientific community is invited to publish their research in the journal. For more information, visit: Revista @limentech.